(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we study the global regularity of logarithmically supercritical MHD equations in 2 dimensional, in which the dissipation terms are -μΛ^2αu and - uL^2β b. We show that global regular solutions in the cases 0 3.